Combining multiple rust resistance genes by phenotypic and marker assisted selection in wheat (Triticum aestivum L.) - Tiwari, Sushma; Tomar, R.S.; Chand, S.; Singh, N.K.; Tomar, S.M.S. (The Indian Journal of Genetics and Plant Breeding, 2017)
Development of cultivars with genetic resistance has been the most effective and economical strategy to control rust diseases of wheat (Triticum aestivum L.). Leaf rust (Puccinia triticina) and stripe rust (Puccinia striiformis) are the two most important diseases of wheat in India. Combining two or more major rust resistance genes into one highly adapted cultivar is one of the important strategies for obtaining durable resistance. Molecular markers have made it possible to identify and pyramid valuable genes of agronomic importance in resistance breeding. The leaf rust resistance genes Lr24, Lr28 and stripe rust resistance gene Yr15 were pyramided into a popular but rust susceptible wheat variety HD2687 using marker assisted backcross breeding. SCAR markers SCS1302607 for Lr24 and SCS421570 for Lr28 and SSR marker Xgwm273 for Yr15 gene were used to select gene positive plants. Different combinations of the three resistance genes were selected in BC4F2 generation of HD2687 with the help of linked molecular markers. Agronomic performance of improved lines was compared with that of the recipient parent.